Peer Tutor Model: Alternative to Improve Student Learning Outcomes in Thematic Learning - Syaflinar, Syaflinar; Azima, Nana Fauzana; Tulljannah, Rahmia; Nur, Farid Muhammad; Pratiwi, Dinda Dwi; Sustarman, Sustarman; Ratih, Maistika (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Learning in elementary schools in Indonesia is carried out thematically, where all subjects are carried out based on the same theme. However, there are many obstacles found in implementing this thematic learning. This research aims to determine the improvement in student thematic learning outcomes in one of the elementary schools in Indonesia. This classroom action research has four components, namely planning, action, observation, and reflection in each cycle. Data collection uses formative test instruments, observation sheets, and field notes. Data analysis uses comparative descriptive techniques. The research subjects were grade 1 elementary school students. The results of the research show that there is an increase in the percentage of student learning activities in each cycle so that the completeness of students' thematic learning outcomes increases. Based on the results of this research, the literacy-based Peer Tutor learning model can improve student thematic learning outcomes.